Unite or face irrelevance. - Rodriguez, R. (IEEE spectrum)
Last May, Sun Microsystems Inc. (Santa Clara, CA) and Red Hat Inc. (Raleigh, NC), which markets a version of the Unix operating system, announced that they would distribute each other's products worldwide. It is a hopeful sign for the information technology industry, but not nearly grand enough. In this article, the author argues that what we really need is for those two companies, along with Apple Computer Inc. (Cupertino, CA), to merge into a hardware-and-software colossus.